Life Cycle Sustainability Assessment of a dish-Stirling Concentrating Solar Power Plant in the Mediterranean area. (October 2021) - Backes, J.G.; D'Amico, A.; Pauliks, N.; Guarino, S.; Traverso, M.; Lo Brano, V.
Highlights: For an existing, grid-feeing CSP plant a cradle-to-use LCSA is performed. LCSA results refer to 35 t CO2 e, production costs and working seconds. The elevation tracker has the highest GWP emissions due to the large use of steel. A detailed risk analysis of critical raw materials was performed via the SHDB. Key challenges were data availability and interpretation of the LCSA results. Abstract: Among the different renewable energy sources, solar energy shows the highest exploitation potential to satisfy a substantial portion of the worlds' future energy demand, guaranteeing at the same time lower emissions than conventional energy providers. Much of this potential is usable thanks to Concentrating Solar Power (CSP) technologies, of which the dish-Stirling concentrator is the most efficient. Nevertheless, the production and installation phases of the dish-Stirling technology can have an environmental impact which motivated the assessment of the plant in the three dimensions of sustainability (environmental, economic and social). The present publication evaluated an existing dish-Stirling plant located in Italy with a Life Cycle Sustainability Assessment. The Life Cycle Assessment resulted in the emission of 35 tons of CO2 e. The main drivers of emissions were the electronic components (16%) and the steel used for the structure (37%). Life Cycle Costing resulted in total costs of 308, 467 € . S-LCA resulted in working seconds for skilled and unskilled workers equal to 1, 454, 400 s and 1, 713, 600 s, respectively. The main challenges that were identified for this work were the data availability for all pillars and the comparability between the actual study and the publications already available in the relevant literature.